2008
DOI: 10.1016/j.jcis.2007.11.028
|View full text |Cite
|
Sign up to set email alerts
|

EXAFS studies on adsorption irreversibility of Zn(II) on TiO2: Temperature dependence

Abstract: Adsorption irreversibility of Zn(II) on TiO 2 at various temperatures was studied using a combination of classical macroscopic methods and extended X-ray absorption fine structure (EXAFS) spectroscopy. When the temperature was increased from 5 to 40 • C, the Zn(II) adsorption capacity increased by 130%, and adsorbed Zn(II) became more reversible. The standard Gibbs free energy change ( G 0 ) of the adsorption reaction at 5, 20, and 40 • C was determined to be −19.58 ± 0.30, −22.28 ± 0.10, and −25.14 ± 0.21 kJ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 43 publications
1
45
0
Order By: Relevance
“…The spectra were processed by removing the background absorbance, normalizing the atomic absorption, and extracting the EXAFS signals from the spectra. The coordination numbers (CN) and interatomic distances (R) were then determined by fitting the model-simulated values to the experimental spectra (Li et al, , 2008Pan et al, 2004).…”
Section: Xafs Data Collection and Analysismentioning
confidence: 99%
“…The spectra were processed by removing the background absorbance, normalizing the atomic absorption, and extracting the EXAFS signals from the spectra. The coordination numbers (CN) and interatomic distances (R) were then determined by fitting the model-simulated values to the experimental spectra (Li et al, , 2008Pan et al, 2004).…”
Section: Xafs Data Collection and Analysismentioning
confidence: 99%
“…The body amplitude reduction factor (S 0 2 ) of 0.87 was used for data fitting. 4,12 The ZnO reference was fitted by use of the Zn-O and Zn-Zn scattering paths calculated from the crystalline structure of ZnO to estimate the accuracies for the fit parameters. All fits were performed in a sequential manner, by adding backscattering paths stepwise and recording reductions of the residual of the fit.…”
Section: X-ray Absorption Fine Structure Measurement and Datamentioning
confidence: 99%
“…The adsorption irreversibility of Zn(II) on anatase at various temperatures was studied using a combination of macroscopic thermodynamic methods and microscopic spectral measurement. Adsorption isotherm results 29 showed that, when the temperature increased from 5 to 40 °C, the Zn(II) adsorption capacity increased by 130% ( Figure 13). The desorption isotherms significantly deviate from the corresponding adsorption isotherms, indicating that the adsorption of zinc onto anatase was not fully reversible.…”
Section: Temperature Dependence Of Metastable-equilibrium Adsorptionmentioning
confidence: 99%
“…The thermodynamic index of irreversibility (TII) proposed by Sander et al 30 was used to quantify the adsorption irreversibility. The TII was defined as the ratio of the observed free energy loss to the maximum possible free energy loss due to adsorption hysteresis, which was given by eq eq eq eq ln ln TII ln ln 29 EXAFS spectra results showed that the hydrated Zn(II) was adsorbed on anatase through edge-sharing linkage mode (strong adsorption) and corner-sharing linkage mode (weak adsorption), which corresponded to two average Zn-Ti atomic distances of 3.25±0.02 and 3.69±0.03 Å, respectively. 29 According to the DFT results (Figure 14), 13 EXAFS measured the corner-sharing linkage mode at the Zn-Ti distance of 3.69 Å may be a mixture of 4-coordinated bidentate binuclear (BB, 3.48 Å) and 6-coordinated monodentate mononuclear (MM, 4.01 Å) MEA states.…”
Section: Temperature Dependence Of Metastable-equilibrium Adsorptionmentioning
confidence: 99%